2006
DOI: 10.1016/j.jde.2005.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Wave equations with time-dependent dissipation I. Non-effective dissipation

Abstract: The goal of this article is to construct structural representations of the solutions to Cauchy problems for weakly dissipative wave equations below scaling and to deduce estimates of the solution and its energy based on L q (R n ), q 2. Furthermore, the sharpness of the obtained estimates is discussed. IntroductionCauchy problems for wave equations with weak dissipationis assumed to be positive and tends to zero as t tends to infinity, provide an important model problem for the study of asymptotic behaviours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
152
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 12 publications
8
152
0
Order By: Relevance
“…The special case µ = 2 + n(2/m − 1) can be easily proved by replacing estimate (40) with (41), whereas estimates (26) and (27) follow from (36) and (37).…”
Section: Proof Of Theorems 4 Andmentioning
confidence: 99%
“…The special case µ = 2 + n(2/m − 1) can be easily proved by replacing estimate (40) with (41), whereas estimates (26) and (27) follow from (36) and (37).…”
Section: Proof Of Theorems 4 Andmentioning
confidence: 99%
“…We refer to [13] for an exposition of results and for the classification of time-dependent dissipation terms. In [18] it was shown that, roughly speaking, under the non-effectivity assumption b(t) = O(t −1 ) E-mail address: wirth@math.tu-freiberg.de. solutions are closely related to free waves.…”
Section: Introductionmentioning
confidence: 99%
“…We refer the reader to [8,9]. On the other hand, if β > 1 then the asymptotic profile of the solution of (1.2) is given by that of the free wave equation w = 0 (see [13]). Wirth [12] considered the linear problem…”
Section: Introductionmentioning
confidence: 99%